Enhanced anticancer effect of thymidylate synthase dimer disrupters by promoting intracellular accumulation - Marverti, Gaetano; Moschella, Maria Gaetana; Belardo, Alice; Lamesta, Michele; Mercanile, Giada; Tagliazucchi, Lorenzo; Aiello, Daniele; Venturelli, Alberto; Illuminati, Davide; Guerrini, Remo; Losi, Lorena; Ponterini, Glauco; et al. (Frontiers in Pharmacology, 2024)
Introduction Thymidylate synthase (TS) plays a crucial role in cellular growth, proliferation, DNA synthesis, and repair, thus gaining attention for targeted therapies in cancer. TS overexpression and the altered pharmacokinetics of anti-TS drugs are among the most prominent causes of cellular resistance. Decreased drug influx and/or efficient efflux result in reduced drug access to the intracellular targets. Results In this study, we have evaluated and demonstrated the increased cytotoxic efficacy of novel TS dimer disrupters (Ddis) in the presence of specific inhibitors of drug efflux protein pumps in ovarian and colon cancer cells, suggesting that these compounds are substrates of the cellular drug extruders. A second strategy adopted to favor intracellular accumulation was to employ, as a drug delivery system, a molecular tool able to help less lipophilic compounds to cross the cell membrane. The Ddis were delivered through the SAINT-Protein transfection agent. The observed cell-killing effects agreed with the reduction of TS protein level and cell cycle perturbation. Conclusion Overall, this preclinical study suggests that the innovative TS dimer disrupters can be optimized by increasing their intracellular accumulation by both inhibiting their outflow and/or enhancing cellular uptake.